Synthesis and Characterization of Flame Retarding UV-Curable Boron Containing Hybrid Coatings - (:unkn) unknown (John Wiley and Sons Inc., 2011)
A series of UV-curable boron containing hybrid coatings prepared by anhydrous sol-gel technique. The chemical structure of hybrid coatings was characterized by FT-IR, RT-IR, 1- NMR and 29Si-CP MAS-NMR techniques. UV curable coatings were applied on polycarbonate substrates. The physical and mechanical properties of UV-cured coatings such as pendulum hardness, pencil hardness, contact angle, gel content, MEK rubbing test, tensile test, abrasion resistance, chemical resistance and flame retardant were examined. Thermal gravimetric analysis (TGA) was made. Results of all analysis conducted on free films and coatings were discussed. The morphology of the hybrid materials was examined by SEM. The hybrids were nanocomposites. © 2011 The Minerals, Metals & Materials Society.
Keywords: Boron; Hybrid; LOI; Sol-gel; UV curing